High land‐use intensity exacerbates shifts in grassland vegetation composition after severe experimental drought. (7th February 2018) - Stampfli, Andreas; Bloor, Juliette M. G.; Fischer, Markus; Zeiter, Michaela
Abstract: Climate change projections anticipate increased frequency and intensity of drought stress, but grassland responses to severe droughts and their potential to recover are poorly understood. In many grasslands, high land‐use intensity has enhanced productivity and promoted resource‐acquisitive species at the expense of resource‐conservative ones. Such changes in plant functional composition could affect the resistance to drought and the recovery after drought of grassland ecosystems with consequences for feed productivity resilience and environmental stewardship. In a 12‐site precipitation exclusion experiment in upland grassland ecosystems across Switzerland, we imposed severe edaphic drought in plots under rainout shelters and compared them with plots under ambient conditions. We used soil water potentials to scale drought stress across sites. Impacts of precipitation exclusion and drought legacy effects were examined along a gradient of land‐use intensity to determine how grasslands resisted to, and recovered after drought. In the year of precipitation exclusion, aboveground net primary productivity (ANPP) in plots under rainout shelters was −15% to −56% lower than in control plots. Drought effects on ANPP increased with drought severity, specified as duration of topsoil water potential ψ < −100 kPa, irrespective of land‐use intensity. In the year after drought, ANPP had completely recovered, but total species diversity had declined by −10%. Perennial species showed elevated mortality, but species richness of annuals showed a small increase due to enhanced recruitment. In general, the more resource‐acquisitive grasses increased at the expense of the deeper‐rooted forbs after drought, suggesting that community reorganization was driven by competition rather than plant mortality. The negative effects of precipitation exclusion on forbs increased with land‐use intensity. Our study suggests a synergistic impact of land‐use intensification and climate change on grassland vegetation composition, and implies that biomass recovery after drought may occur at the expense of biodiversity maintenance. Abstract : Severe experimental drought reduced productivity irrespective of land‐use intensity across multiple grasslands. Recovery of grass growth after drought, possibly enhanced by nutrient pulses stabilized community productivity after drought. Community structure was more sensitive to drought than productivity. Reductions in biomass response ratios of forbs were amplified with increasing land‐use intensity.